Development to Angkor Performance Training Course of High School Students - Paitoon, Koranit; Suntharanont, Rojana; Suntharanont, Kamron (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2025)
This research aimed to: 1) develop and evaluate the qualities of Aeng Gor performing arts training curriculum for high school students, 2) compare the academic achievement in Aeng Gor performing arts knowledge of high school students before and after learning, 3) study the academic achievement in Aeng Gor performing arts practical skills, and 4) study the satisfaction towards the Aeng Gor performing arts training curriculum. This research was experimental research with a one-group pretest-posttest design. The sample group used in the research was 30 high school students at Salokbat Witthaya School, who volunteered to participate in the training. The research tools consisted of: 1) a questionnaire on needs, 2) a curriculum quality assessment form, 3) a learning management plan, 4) an academic achievement test, 5) a practical skills assessment form, and 6) a satisfaction questionnaire. The statistics used in data analysis were mean, standard deviation, percentage, and t-test. The results showed that: 1) the qualities of the Aeng Gor performing arts training course were in the most appropriate overall, 2) the learning achievements in knowledge of Aeng Gor performing arts after studying were higher than before studying, 3) the learning achievement in practical skills of high school students in Aeng Gor performing arts was at a very good level overall, 4) the satisfaction of high school students towards the Aeng Gor performing arts training curriculum was at the highest level.